Crime in the smog: An analytical study of the haze problem in Northern Thailand through the lens of green criminology - Klinfung, Thanaporn (Journal of Thai Ombudsman, 2026)
Haze has been a matter of serious concern in Thailand since 2007, and over the past two decades, the impacts of this problem have become increasingly severe, particularly in the country’s northern region, which is rich in forests and agricultural land. Historically, efforts to manage the haze problem have primarily been based on an environmental management perspective. However, this article aims to present a paradigm shift in addressing the haze issue through the conceptual framework of “Green Criminology.” By utilizing documentary analysis, it explains how this problem can be considered a type of environmental crime. From the perspectives of rational choice theory and deterrence theory, it is found that agricultural burning stems from perpetrators weighing the costs and benefits, with economic incentives serving as a primary factor that allows the problem to persist. Currently, there are no specific laws addressing these actions. Meanwhile, existing legal mechanisms and regulations, despite being enforced, remain ineffective because economic incentives influence the offenders’ decision-making far more than the fear of the law. Consequently, tackling the haze problem should be reframed as an issue of environmental crime. Nevertheless, managing this problem must also focus on systemic solutions rather than solely penalizing individuals at the end of the chain. For instance, supportive measures should be increased to reduce the economic incentives for farmers and/or entrepreneurs to engage in open burning, which would make law enforcement mechanisms more effective. This includes enacting laws that incorporate Extended Producer Responsibility within contract farming systems and linking these efforts to Green Finance initiatives, among other measures.